Describing the Sigmoidal Behavior of Roasted White Lupin (Lupinus albus) During Hydration - Augusto, PED (2017)
The authors are grateful to the S~ao Paulo Research Foundation (FAPESP, Brazil) for funding the project No. 2014/16998-3, the National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project No. 401004/2014-7, and Cienciactiva for the A.C. Miano PhD scholarship, from the “Consejo Nacional de Ciencia, Tecnologıa e Inovacion Tecnol ogica (CONCYTEC, Peru; Contract 272-2015-FONDECYT).